Emergence of West Nile virus lineage 2 in Europe: Characteristics of the first seven cases of West Nile neuroinvasive disease in horses in Austria - de Heus, Phebe; Kolodziejek, Jolanta; Camp, Jeremy V; Dimmel, Katharina; Bagó, Zoltán; Hubálek, Zdenek; van den Hoven, René; Cavalleri, Jessika-M V; Nowotny, Norbert (Transboundary and emerging diseases, 2020)
We report details of the first seven equine cases of confirmed West Nile neuroinvasive disease in Austria. The cases presented during summer and autumn of 2016 (n = 2), 2017 (n = 3) and 2018 (n = 2). All horses showed gait abnormalities and 6 of 7 horses exhibited fasciculations and/or tremors, and we provide video recordings of these. Three horses also showed cranial nerve involvement. Following rapid improvement, three horses were discharged. Four horses were euthanized due to the severity of clinical signs and subjected to neuropathological examination. West Nile virus (WNV) lineage 2 nucleic acid was detected in 5 of 7 horses, and WNV-specific neutralizing antibodies in all 7 horses. In addition, serologic evidence of WNV infection was found in two out of fourteen in-contact horses. Horses may be considered a sentinel species for human WNV infections, integrating human and veterinary medicine and thus contributing to the one health concept.
Keywords: sentinelové organismy; fatální výsledek; nemoci koní; West Nile Fever; Sentinel Species; West Nile virus; západonilská horečka; Horses; Female; virus západního Nilu; koně; zvířata; Rakousko; Austria; ženské pohlaví; Male; Horse Diseases; Animals; Fatal Outcome; mužské pohlaví